Emergence of collective behavior in a system of autonomous agents - I. Antoniou; F. Bosco; V. V. Ivanov; I. V. Kisel (Discrete Dynamics in Nature and Society)
We study the properties of emergent collective behavior in a system of interacting autonomous agents. The system evolves in time according to two rules of communication, one from interactions between agents and another one from interactions of the agents with an additional agent which evolves in time in a periodic and stable manner. The application of these two rules is decided by a prescribed probability distribution. We analyze the emergence and the efficiency (coordination) with which collective patterns are constructed in time as a function of the parameters of the system.